Tax-to-GDP Ratio and the Relation of Tax Revenue with GDP: Nepalese Perspective - Dahal, Arjun Kumar (Researcher: A Research Journal of Culture and Society, 2020)
This study aims to show the tax-to-GDP ratio condition and explore the relation of tax revenue with Nepal's GDP. It is based on the secondary data that is collected from various published sources. Descriptive and exploratory research designs are used to explore the relationship between tax revenue and GDP. Some statistical and econometric tools like mean, depression, correlation, Johnsen Co-integration Test, Vector Error Correction Model (VECM), serial correlation, heteroskedasticity test, and normality test are used. There is a high degree of the positive relationship between tax revenue and GDP of Nepal. The tax revenue and GDP are co-integrated, or they have a long-run association ship. The tax-to-GDP ratio of Nepal lies in the high rank among the various developing countries. So, tax to GDP ratio alone cannot ensure its economic growth. It is advised to the concerned authorities to increase the income to increase the tax revenue; otherwise, it increases the general public's dissatisfaction with the government.